Penerapan Terapi Relaksasi Otot Progresif Terhadap Tekanan Darah Pada Lansia Dengan Hipertensi - Septiana Dwi Eka Wahyuningsih; Riyani Wulandari (Jurnal Anestesi, 2023)
Background; Hypertension is a "sillent killer" disease that is mostly experienced by the elderly. According to data from the World Health Organization (WHO) in 2021, the prevalence is 1.28 billion people with hypertension aged 30-79 years. The prevalence of the elderly in the world and Indonesia continues to increase because the elderly experience a decline in physical conditions, including the cardiovascular system, which increases the risk of degenerative diseases such as hypertension. Therefore, progressive muscle relaxation can be used as an alternative therapy for the elderly with hypertension. The Objectives of the research; Knowing the results of the implementation of progressive muscle relaxation on blood pressure in the elderly with hypertension. Method; This application uses a case study method by observing blood pressure in two elderly respondents. The instruments used are observation sheets, sphygmomanometer, and stopwatch. Results; After application for 20 minutes with a frequency of four times a week for two consecutive weeks showed a decrease in blood pressure in both respondents to prehypertension. Summary; Progressive muscle relaxation therapy can potentially reduce blood pressure in the elderly with hypertension.